Management of refractory hepatic hydrothorax: a report of two cases and review of the literature - Calixto-Aguilar, Lesly (2024)
Hepatic hydrothorax is a transudative pleural effusion in patients with cirrhosis. A 56-yearold cirrhotic patient presented with dyspnea and desaturation; his chest images showed a right pleural effusion. Another 66-year-old woman with cirrhosis, developed during her hospitalization acute respiratory failure, and her chest X- ray showed left pleural effusion. Initially, both patients were prescribed a dietary sodium restriction and diuretics. Nevertheless, they didn’t have a good response so a chest tube was placed, and an octreotide infusion partially reduced the volume of the pleural drainage allowing a pleurodesis. We report two cases of refractory hepatic hydrothorax with multiple treatments including octreotide and pleurodesis.